Government Inside Information and Debt Signaling: Evidence from Consumer and Business Confidence. - Hirata, Sean C. (Tufts Archival Research Center, 2005)
My research begins with a new theoretical model that applies the idea of debt signaling to the public sector. It suggests that due to constraints on the government's time in power, spending as much as possible in the current period is attractive as long as the government doesn't default in the future. Therefore, a strong projection of economic growth would lead to an increase in deficit spending in the current period. Using U.S. public debt to GDP ratio and measures of consumer and business confidence, I look at whether an increase in debt is taken to be a signal of future growth, as it is in the private sector. To do this, I estimate two versions of a two variable VAR model, one for consumer confidence and one for business confidence. In both models, I find evidence that supports the theoretical model with a positive significant impact of debt on confidence.